2017
DOI: 10.1111/jvh.12790
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 208‐week sequential therapy with telbivudine and entecavir in HBeAg‐positive chronic hepatitis B patients with suboptimal responses to 24 weeks of Peg‐IFNα‐2a therapy: An open‐labelled, randomized, controlled, “real‐life” trial

Abstract: The purpose of the study was to compare the efficacy and safety of 208-week sequential therapy with telbivudine and entecavir in HBeAg-positive chronic hepatitis B (CHB) patients with suboptimal responses to 24 weeks of Peg-IFNα-2a therapy. This was an open-label, randomized, controlled, "real-life" trial. HBeAg-positive CHB patients with serum HBV DNA ≥5.0 lg IU/mL and a < 1 lg IU/mL decline of HBsAg level from baseline who underwent at least 24 weeks of Peg-IFNα-2a therapy were included. Enrolled patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Peg-IFN-α-2b combination with ADV therapy inhibited viral productivity by 99% and subsequent ADV monotherapy by 76%, while with only a small number of patients involved (24 patients), this clinical trial is limited ( Lutgehetmann et al, 2008 ). Switch to TBV after 24 weeks of Peg-IFNα-2a therapy was shown to promote HBeAg seroconversion that merits investigation in HBeAg-positive CHB patients ( Luo et al, 2017 ). Sequential approaches with peg-IFN and NUCs were also tested, however, no significant benefit was noted ( Xie et al, 2014 ; Brouwer et al, 2015 ).…”
Section: Rational For Ifn-based Treatment Of Chronic Hepatitis Bmentioning
confidence: 99%
“…Peg-IFN-α-2b combination with ADV therapy inhibited viral productivity by 99% and subsequent ADV monotherapy by 76%, while with only a small number of patients involved (24 patients), this clinical trial is limited ( Lutgehetmann et al, 2008 ). Switch to TBV after 24 weeks of Peg-IFNα-2a therapy was shown to promote HBeAg seroconversion that merits investigation in HBeAg-positive CHB patients ( Luo et al, 2017 ). Sequential approaches with peg-IFN and NUCs were also tested, however, no significant benefit was noted ( Xie et al, 2014 ; Brouwer et al, 2015 ).…”
Section: Rational For Ifn-based Treatment Of Chronic Hepatitis Bmentioning
confidence: 99%
“…The results of RCTs have shown that telbivudine was superior to lamivudine in the treatment of patients with chronic HBV regardless of HBeAg status. [37][38][39] In addition, results from several RCTs have shown the superiority of telbivudine over other NUCs such as entecavir 40,41 and adefovir. 42 However, in 2013, Tsai et al found that the cumulative incidence of HCC development in patients treated with telbivudine was 2.5% and 4.1% at two and three years, respectively which was not statistically different from the results of patients treated with entecavir (3.1% and 7.5% at two and three years respectively; P ¼ 0.565).…”
Section: Lamivudine Risk Of Hcc After Treatment With Nucleos (T)ide Amentioning
confidence: 99%
“…The results of RCTs have shown that telbivudine was superior to lamivudine in the treatment of patients with chronic HBV regardless of HBeAg status. 3739 In addition, results from several RCTs have shown the superiority of telbivudine over other NUCs such as entecavir 40,41 and adefovir. 42 However, in 2013, Tsai et al.…”
Section: Introductionmentioning
confidence: 99%
“…Seroconversion to this antigen and subsequent antigen loss (HBeAg negative status, anti-HBe positive phase) is associated with reduced viral replication and diminished long-term complications, for example, the risk of hepatocellular carcinoma 18 . Progression to seroconversion, either spontaneous or treatment-induced, may take years; contemporary studies have demonstrated differential rates of seroconversion associated with the duration and type of therapeutic regimen in addition to individual patient clinical profiles 19,20 . All virological factors associated with HbeAg seroconversion have not been elucidated and deeper knowledge of these may aid the definition of patients likely to seroconvert and direct appropriate therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%